Pharmacokinetics and Bioequivalence of Doxycycline (Providox® and Doxyvet 0-50 S®) Oral Powder Formulations in Chickens - Hantash, Tariq M.; Abu-Basha, Ehab A.; Roussan, Dergham A.; Abudabos, Alaeldein M. (International Journal of Poultry Science, 2008)
A bioequivalence and pharmacokinetics profiles of two doxycycline powder formulations (Providox® and Doxyvet 0-50 S®) were compared in 24 healthy chickens following administration of a single oral dose (20 mg/kg bw). Serial blood samples were drawn at 10 points after administration to determine doxycycline concentrations in chicken plasma by HPLC/UV. the pharmacokinetics parameters; area under plasma concentration-time curve (AUC0-24), maximum plasma concentration (Cmax) were determined for both formulations. The average means of AUC0-24 and Cmax for Providox® and Doxyvet 0-50 S® were very close (62.32 ± 3.34 and 57.55 ± 4.66 µg.h/ml and 5.36 ± 0.26 and 5.08 ± 0.25 µg/ml, respectively) with no significant differences based on ANOVA. The 90% confidence intervals of the parameters AUC0-24 and Cmax between two formulations were within the range 80 to 125 % of bioequivalence according to US FDA regulation. The relative bioavailability of Providox® compared to Doxyvet 0-50 S® was 108.24%. Therefore, the Providox® and Doxyvet 0 - 50 S® were considered to be bioequivalent.